1997
DOI: 10.1159/000264493
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Differentiate between Choledochal Cyst and Congenital Biliary Atresia (Type I Cyst) by Antenatal Ultrasonography?

Abstract: Both choledochal cyst and congenital biliary atresia (type I cyst) may share the same ultrasonographic pattern. We report 2 cases which were shown to have cystic structures on the upper abdomen by antenatal ultrasonography. The size of the choledochal cyst found at 24 weeks’ gestation increased steadily as gestational age advanced. But the size of the cyst in congenital biliary atresia found at 29 weeks’ gestation remained unchanged throughout the remaining pregnancy. Cyst enlargement, therefore, may suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 6 publications
3
24
0
2
Order By: Relevance
“…Among 50 infants with type 1 BA, 38 were described as cystic; however, cystic change in infants with a higher level of obstruction may not have been reported. Cysts of the biliary tract can be detected sonographically in the fetus [4,7,8,10,11,13,16,17]. In our series, detection was facilitated by larger cyst size, as anticipated, which led to earlier surgery.…”
Section: Discussionsupporting
confidence: 64%
“…Among 50 infants with type 1 BA, 38 were described as cystic; however, cystic change in infants with a higher level of obstruction may not have been reported. Cysts of the biliary tract can be detected sonographically in the fetus [4,7,8,10,11,13,16,17]. In our series, detection was facilitated by larger cyst size, as anticipated, which led to earlier surgery.…”
Section: Discussionsupporting
confidence: 64%
“…Some authors have reported characteristics of cysts in the biliary tree as indicators for the diagnosis of BA or CC. Matsubara et al reported that enlargement of the cyst suggests the possibility of CC [7]. On the other hand, Casaccia et al reported that a small anechoic cyst in the hepatic hilum is suspicious of BA [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although magnetic resonance imaging (MRI) or threedimensional (3D) US with reconstructed planes may aid the prenatal diagnosis, we believe that a careful and precise twodimensional (2D) US should be encouraged, since it may be satisfactory enough, in most cases, to demonstrate the sign of the connection between the gall bladder and the cyst, like in our case [10][11][12][13][14][15]. Indeed, MRI as well as 3D technology, although can be very useful in many cases, especially those of unfavourable fetal position, are expensive tools, require expert operators and are not readily available in some clinical contexts.…”
Section: Gynecology and Obstetrics Case Report Issn 2471-8165mentioning
confidence: 88%